A Detailed Cutaneous Manifestations Evaluation in Patients with Polycystic Ovary Syndrome - Masaeli, Asiyeh; Nayeri, Hashem; Mirzaei, Mohammadreza (Archives of Medical Laboratory Sciences, 2021)
Background and Aim: Polycystic ovary syndrome (PCOS) is the most common endocrine disorder among women of reproductive age. The hypothalamus-pituitary-ovary axis dysregulates in PCOS, ultimately leading to hyperandrogenisms. Consequently, it is associated with hirsutism, dyslipidemia, obesity, infertility, menstrual disturbance, and insulin resistance. To our knowledge, there is no detailed investigation of these manifestations. That is why, this study aimed to evaluate manifestations of hyperandrogenism, hirsutism in particular. Methods: This study was performed on 39 women with an initial diagnosis of polycystic ovary syndrome. Rotterdam criteria including Oligo- or anovulation, hyperandrogenism clinical and/or biochemical signs, and ultrasound appearance of polycystic ovaries used as diagnostic criteria. Hirsutism scoring was carried out according to Freeman-Gallwey’s definition of hirsutism. The patients were analyzed for other skin problems including male pattern baldness, acanthosis nigricans, and acne as well as demographic features. Results: Hirsutism was observed in the majority of our patients (91%) ranging from mild to severe. Concerning the distribution of hirsutism on various parts of the body, severe hirsutism was observed more on the groin, abdominal area, and chin respectively. Male pattern baldness, acanthosis nigricans, and acne, and dysregulated menstruation were reported in these patients. Conclusion: This investigation found that skin manifestations, especially hirsutism, are highly frequent in patients with PCOS. *Corresponding Author: Hashem Nayeri; Email: hnaieri@gmail.com; nayeri@iaufala.ac.ir Please cite this article as: Masaeli A, Nayeri H, Mirzaei M. A Detailed Cutaneous Manifestations Evaluation in Patients with Polycystic Ovary Syndrome. Arch Med Lab Sci. 2021;7:1-6 (e10). https://doi.org/10.22037/amls.v7.30828